History of turkish press - Есбосынов, Е. З.; Мaхсутовa A. (Journal of Oriental Studies, 2018)
The aim of the article is to identify the reasons that contributed to the emergence, development and establishment of the press as a complete and mandatory social institutions of modern society. Syndicate as a means to an end, in ancient times, the press used to declare people of different notifications, through various media, as we know, they have the same age of human history. During the peak of the Ottoman Empire, Venice newspaper was a real breakthrough in journalism, which contributed to the development of professionalism in the field of printing.